Predicting Meningioma Risk: The Role of Hormone-Related Molecular Markers and Intracellular Signaling Pathways - Sari Sulistyoningsih; Miranda Aisah; Utter Prakesh; Bryan Helsey (Phlox Institute: Indonesian Medical Research Organization, 2025)
Introduction: Meningiomas are common intracranial tumors with an established association with hormonal factors. This study aimed to comprehensively evaluate the predictive value of hormone-related molecular markers and their associated intracellular signaling pathways in meningioma development. Methods: A retrospective case-control study was conducted, including 200 patients with histologically confirmed meningioma (cases) and 200 age- and gender-matched controls. Tumor tissue and serum samples were analyzed for the expression of estrogen receptor (ER), progesterone receptor (PR), androgen receptor (AR), and growth hormone receptor (GHR) using western blot and ELISA, respectively. The activation status of the PI3K/AKT/mTOR and MAPK/ERK signaling pathways was assessed by analyzing the levels of phosphorylated proteins in the pathways. Results: Elevated expression of ER, PR, and GHR was observed in the tumor tissue of meningioma cases compared to controls (p<0.05). Serum levels of ER and PR were also significantly higher in cases. Analysis of signaling pathways revealed increased activation of both PI3K/AKT/mTOR and MAPK/ERK pathways in meningioma cases. Multivariate analysis confirmed that ER and PR expression, both in tumor tissue and serum, were independent predictors of meningioma risk, along with age and female sex. Conclusion: Our findings suggest that ER, PR, and GHR may serve as potential predictive markers for meningioma risk. The involvement of PI3K/AKT/mTOR and MAPK/ERK signaling pathways further underscores the complex interplay between hormonal factors and intracellular signaling in meningioma development. These findings may contribute to improved risk assessment and the development of targeted therapeutic strategies for meningiomas.